Reconstruction of the absorbed dose of ionizing radiation for helophytes in the water bodies of the near emergency zone at the Chornobyl NPP - V. V. Belyaev; O. M. Volkova; D. I. Gudkov; S. P. Pryshlyak (Ядерна фізика та енергетика)
Based on modeling the dynamics of the Chornobyl emission radionuclide content in the components of the most polluted reservoirs of the Chornobyl Exclusion Zone, the absorbed dose for helophytes was reconstructed. During the growing season of 1986, the absorbed dose of plants of Glyboke Lake was 78 Gy, Daleke Lake 39 Gy. The absorbed dose rate of plant roots was 2.4 times higher than that of aboveground organs. According to actual data, in the period 2016 - 2019 in the Glyboke Lake average dose of external and internal plant irradiation was about 7.5 mGy/year, and in the Daleke Lake 5.6 mGy/year. On abnormally contaminated sections of the Glyboke Lake, the external dose reaches 0.5 - 1.0 Gy/year. During the period 1986 - 2020, the maximum cumulative (biological) dose of helophytes of Glyboke Lake can be 190 Gy, Daleke Lake 80 - 85 Gy.